2017
DOI: 10.14719/pst.2017.4.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Anti-platelet aggregation effects of extracts from Arbutus unedo leaves

Abstract: It is well known that platelet hyperactivity is a risk factor for cardiovascular diseases such as atherosclerosis, stroke and myocardial infarction. This study aimed to examine the effects of extracts enriched in flavonoids obtained from Arbutus unedo leaves on platelet aggregation. Rat platelets were prepared and incubated in vitro with different doses of the tested extracts, and aggregation was trigged by physiological agonists. Platelet treatment with increasing concentrations (0.1 -1 mg/ml) of diethyl ethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…The involvement of such compounds in hemostasis was already initiated in our laboratory. Flavonoids (genins and heterosidic flavonoids) isolated from Arbutus unedo [ 33 ] or Petroselinum crispum [ 6 ] inhibit platelet aggregation. More, Gadi et al [ 6 ] reported that the adhesion of human platelets to collagen under flow was greatly decreased by genins of Petroselinum crispum .…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of such compounds in hemostasis was already initiated in our laboratory. Flavonoids (genins and heterosidic flavonoids) isolated from Arbutus unedo [ 33 ] or Petroselinum crispum [ 6 ] inhibit platelet aggregation. More, Gadi et al [ 6 ] reported that the adhesion of human platelets to collagen under flow was greatly decreased by genins of Petroselinum crispum .…”
Section: Discussionmentioning
confidence: 99%
“…For polyphenols, flavonoids present a large group of natural products, widely distributed in plant, and exhibit an antiaggregant 29 and antithrombotic activities 30 . Some hypothesis are evoked to explain the antithrombotic activity of polyphenols such us inhibition of key enzymes involved in platelet function; cyclooxygenase and lipo-oxygenase 31 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that genins (free flavonoids) hetrosidic flavonoids reduced significantly thrombin-induced platelet aggregation with IC50 values of 0.22 ± 0.03 and 0.36 ± 0.05 mg/ml, respectively. In addition, at 1 mg/ml, these compounds reduced significantly the initial rate of platelet aggregation by 97.8 ± 0.74% and 90.8 ± 1.55% for genins and heterosidic flavonoids, respectively [ 44 ]. Thus, these findings clearly demonstrate that the anti-platelet effect of A. unedo is mainly attributed to flavonoids.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…According to different toxicity tests, the use of A. unedo is devoid of any significant side effects and/or toxicity. Indeed, in an acute toxicity test performed in mice, we have demonstrated that the oral administration of A. unedo leaf aqueous extract at a dose up to 1200 mg/kg caused no mortality and no signs of adverse effects, demonstrating that the LD 50 value of the A. unedo aqueous extract was higher than 1200 mg/kg b.w in oral administration in mice [ 44 ]. In another acute toxicity test realized in mice, it has been reported that the A. unedo root aqueous extract exhibited LD 50 higher than 2000 mg/kg b.w with no adverse effect of this dose shown after single oral administration in mice [ 76 ].…”
Section: Toxicological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation